Germany's colonial pasts - Ames, Eric, 1969-; Klotz, Marcia, 1961-; Wildenthal, Lora, 1965- (Lincoln : University of Nebraska Press, 2005)
'Germany's Colonial Pasts' is a wide-ranging study of German colonialism and its legacies.
Foreword / Sander L. Gilman -- Introduction / Marcia Klotz -- Colonialism and the culture of respectability / Woodruff D. Smith -- Inventing the Auslandsdeutsche: emigration, colonial fantasy, and German national identity, 1848-71 / Bradley D. Naranch -- The colonialist beginnings of comparative musicology / Vanessa Agnew -- Race, gender, and sexuality in German Southwest Africa: Hans Grimm's Südafrikanische Novellen / Sara Lennox -- Constructing racial difference in colonial Poland / Kristin Kopp -- Colonization and modernization: the legal foundation of the colonial enterprise--a case study of German colonization in Cameroon / David Simo -- What does German colonialism have to do with national socialism? A conceptual framework / Pascal Grosse -- The Weimar Republic: a postcolonial state in a still-colonial world / Marcia Klotz -- Theology as a vision for colonialism: from supersessionism to dejudaization in German Protestantism / Susannah Heschel -- Race power in postcolonial Germany: the German Africa Show and the national socialist state, 1935-40 / Elisa von Joeden-Forgey -- Marching in step: German youth and colonial cinema / Robert Gordon and Dennis Mahoney -- Autobiographical accounts of Kenyan-German marriages: reception and context / Nina Berman -- Autobiographies of blackness in Germany / Patrice Nganang.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: German literature -- 19th century -- History and criticism; German literature -- 20th century -- History and criticism; Nationalism -- Germany -- History; National characteristics, German, in literature; Imperialism -- History -- 19th century; Germany -- Foreign relations -- 1918-; Colonies in literature; Nationalism in literature; Germans in literature; Littérature allemande -- 19e siècle -- Histoire et critique; Littérature allemande -- 20e siècle -- Histoire et critique; Nationalisme -- Allemagne -- Histoire; Allemands dans la littérature.; Impérialisme -- Histoire -- 19e siècle.; Colonies dans la littérature.; Nationalisme dans la littérature.; Allemagne -- Relations extérieures -- 1918-; LITERARY CRITICISM -- European -- German; Germans in literature; Colonies in literature; Diplomatic relations; German literature; Imperialism; National characteristics, German, in literature; Nationalism; Nationalism in literature; Germany; Literatur; Kolonialismus; Kolonialismus; Kultur; Deutschland; Duitse koloniën.; Kolonialisme; Deutsch; 15.50 general world history; history of great parts of the world, peoples, civilizations: general; Since 1800; German colonialism; Criticism, interpretation, etc; History; Aufsatzsammlung